Improving Students' Mathematics Learning Outcomes Through the Implementation of PAIKEM: A Classroom Action Study in Elementary Schools - Dyah Anungrat Herzamzam; Satria Indra Kusuma; Diani Putri Utami; Chrisnaji Banindra Yudha (International Journal of Education and Learning Studies, 2025)
Improving students' mathematics learning outcomes requires the application of learning models that make students active, innovative, and creative, as well as effective and enjoyable, one of which is the PAIKEM model (Active, Innovative, Creative, Effective, and Enjoyable Learning). This classroom action research aims to improve students' mathematics learning outcomes through the application of the PAIKEM model. This research was conducted in an elementary school in the odd semester of the 2021/2022 academic year. The research design followed the Kemmis and Taggart model, which consists of planning, action, observation, and reflection in two cycles. Data collection techniques used observation, interviews, tests, and documentation, with the research subjects being fifth-grade students. Data were analyzed descriptively quantitatively and qualitatively. The results showed that the PAIKEM model succeeded in significantly improving students' mathematics learning outcomes. This was indicated by an increase in classical learning completeness from 85% in Cycle I to 100% in Cycle II. Thus, it can be concluded that the PAIKEM model is effective in improving mathematics learning outcomes in elementary schools.